2008
DOI: 10.4103/0250-474x.41466
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of <i> Vitex trifolia</i> against carbon tetrachloride-induced hepatic damage

Abstract: Aqueous and ethanol extracts of leaf of Vitex trifolia was investigated for hepatoprotective activity against carbon tetrachloride induced liver damage. To assess the hepatoprotective activity of the extracts, various biochemical parameters viz., total bilirubin, total protein, alanine transaminase, aspartate transaminase and alkaline phosphatase activities were determined. Results of the serum biochemical estimations revealed significant reduction in total bilirubin and serum marker enzymes and increase in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Concurrently, the effect of SY on liver cells suggests that the hepatoprotective action is due to the presence of flavonoids and phenols and their regenerative ability and its antioxidant effects [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, the effect of SY on liver cells suggests that the hepatoprotective action is due to the presence of flavonoids and phenols and their regenerative ability and its antioxidant effects [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Using various in vivo and in vitro models, some of the plants used in Rwanda, or other species from the same genus, have been previously investigated against an hepatotoxicity induced (i) by CCl 4 in rats and/or mice (Hypoestes triflora, Acanthus ilicifolius, Solanum nigrum, Leucas hirta, Indigofera sp., Myrica rubra) (Van Puyvelde et al, 1989;Babu et al, 2001;Singh et al, 2001;Manjunatha et al, 2005;Shahjahan et al, 2005;Singh et al, 2006;Lin et al, 2008;Mukherjee et al, 2009;Xu et al, 2009); (ii) by CCl 4 and dgalactosamine in rats (Ocimum gratissimum and Ocimum basilicum) (Lin et al, 1995); (iii) by CCl 4 and acetaminophen in rats and/or mice (Vernonia amygdalina, Carica papaya, Bidens pilosa) (Babalola et al, 2001;Rajkapoor et al, 2003;Iwalokun et al, 2006;Yuan et al, 2008); (iv) by acetaminophen and thioacetamide in rats (Hygrophila auriculata) (Singh and Handa, 1995;Shanmugasundaram and Venkataraman, 2006); (v) by CCl 4 , acetaminophen, ethanol, dgalactosamine, iron and Amanita phalloides in rats and mice (Silybum marianum) (Chih et al, 1996;Pradhan and Girish, 2006); and (vi) by CCl 4 and acetaminophen in guinea pigs and rats (Ocimum lamiifolium, Crassocephalum vitellinum, Guizotia scabra and Vernonia lasiopus) (Mukazayire et al, 2010). An antihepatitis C activity has also been demonstrated for Embelia schimperi that acts on the HCVProtease (Hussein et al, 2000).…”
Section: Herbal Recipes For the Therapy Of Liver Diseasesmentioning
confidence: 99%
“…In this review article, an attempt has been made to compile the reported hepatoprotective plants from India or abroad and may be useful to the health professionals, scientists and scholars working in the field of pharmacology and therapeutics to develop evidence-based alternative medicine to cure different kinds of liver diseases in men and animals. Vitex trifolia [82] Leaf Aqueous and ethanol Persicogenin, artemetin, luteolin, penduletin and chrysosplenol-D Decreases the rise of serum enzymes and total protein level in liver Vitis vinifera [83] Leaves Ethanol Halimane-type diterpenes, vitetrifolins…”
Section: Flavonoids and Biflavonoidsmentioning
confidence: 99%